The Early Days of Architectural Psychology in The United Kingdom: An Intellectual Autobiography - David Canter (DEPARCH Journal of Design Planning and Aesthetics Research)
The personal history is described, stating in the late 1960’s, that gave rise to an involvement in architectural, and later environmental psychology. This includes both the research activity and the emergence of a theoretical perspective of people’s active involvement in their surroundings that has been the basis of subsequent research and professional activity. The impact of particular areas of application, notably the study of human activities when caught in a building on fire, and other emergencies, facilitated the emergence of the concept of environmental roles and rules, which enriched the developing Psychology of Place theory. This autobiographical account leads to the unexpected involvement in the early 1990’s in contributing to police investigations. As in all autobiographies it is a work in progress, looking back in order to gain some understanding of the future.